Numerical Code-Switching in Khuzestani Arabic - Matoori, Hossein (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This paper aims to pinpoint a case of language contact in Khuzestani Arabic- a vernacular spoken in southwest of Iran- where Iranian Khuzestani Arab bilinguals use code-switching in their conversations with numbers. There has not been much research on Khuzestani Arabic vernacular particularly from a sociolinguistics point of view. The way Khuzestani Arabs switch from Arabic to Persian (Farsi) when incorporating numbers into their conversations has triggered the main impetus for this research. After studying and analyzing some samples of their speech, it has been found that this code-switching is surprisingly systematic and rule-governed. The result of this study shows that when scale is assigned to numbers describing weight, height, distance, price, and age, they are said in Arabic; whereas non-scale numbers describing digits, codes, contact numbers, serial numbers, or credit card numbers are said in Persian.